Analisis Pengaruh Intellectual Capital (IC) Terhadap Kinerja Lembaga Zakat - Ahmad Daelami; Rininta Nurrachmi; Zulkarnain Muhammad Ali (IRTIQO' : Postgraduate Journal of Islamic Economics, Finance and Accounting Studies, 2023)
The realization of zakat collection in Indonesia is still low compared to the potential collection. This is an irony because Indonesia is a country with a majority Muslim population. The causes are the low public trust in Zakat Management Organization (OPZ) and the internal and external problems faced by the institution. This study aims to analyze the effect of intellectual capital on the performance of zakat institutions. Data analysis methods in this study using Structural Equation Modeling (SEM). The results of this study show that there are 3 IC variables that affect the performance of zakat institutions, namely the first relational capital where the organization must improve services to encourage muzakki satisfaction and loyalty and expand the network of partners who support the organization's operations. Second, Social Capital where the organization needs to have organizational values and organizational culture that are internalized to all amil zakat in the organization to encourage better organizational performance. Third, Spiritual Capital as an Islamic-based NPO, zakat institutions must encourage each amil in the institution to have a good level of religiosity and apply ethical values according to Islamic law. The 3 IC variables consisting of HC, STC and TC have no effect on the performance of zakat institutions.